Ноктюрн: веросъёс / Вячеслав Ар-Серги - Ар-Серги Вячеслав Витальевич (Удмуртия, 2003)
Экземпляры: аб. ЦБ (2004) / Инвентарный номер: 51217 / Цена: / Сис.шифр: С(Удм) / Авт.знак: А 85 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)